Methods of testing plastics. Chemical properties. Determination of pH of water extract of polyolefin compound. Determination of water-soluble sulphates in polyolefin compound. Determination of water-soluble chlorides in polyolefin compound Part 4, (31st January 1978) - British Standards Institution,
No abstract available